Wireless Communication on PLC Using Access Point TP-Link TL-WN722N - Rendi Priyatna; Asep Andang; Firmansyah Maulana Sugiartana Nursuwars (Journal of Electrical Technology UMY, 2021)
Technological developments are a requirement for more practical system operation. One example is in data transmission. Wireless data communication is currently very popular. In today's revolution 4.0, of course, the use of cables in data transmission media is rarely used, but not every device supports wireless data communication. One of them is the PLC (Programable Logic Controller). As for additional extensions for PLCs to communicate wirelessly, they are sold separately and, of course, the price is quite expensive. Therefore, a solution for PLCs to communicate wirelessly using the TL-WN722N access point is widely available on the market. Measurements are made with the concept of point to point by looking at the results of modbus scans using Modscan32 on a PC server. The results show that the optimal maximum distance is 80 meters, with an average data transmission time of 1 second.